2010 IEEE International Conference on Robotics and Automation 2010
DOI: 10.1109/robot.2010.5509601
|View full text |Cite
|
Sign up to set email alerts
|

Automation of tissue piercing using circular needles and vision guidance for computer aided laparoscopic surgery

Abstract: Abstract-Despite the fact that minimally invasive robotic surgery provides many advantages for patients, such as reduced tissue trauma and shorter hospitalization, complex tasks (e.g. tissue piercing or knot-tying) are still time-consuming, errorprone and lead to quicker fatigue of the surgeon. Automating these recurrent tasks could greatly reduce total surgery time for patients and disburden the surgeon while he can focus on higher level challenges. This work tackles the problem of autonomous tissue piercing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…The actions to test the collaborative robot take into account the various robotic actions covered by the literature [20], among which are the guidance of the laparoscopic camera for the safe movement of the endoscope [21] or a needle insertion [22], the prediction of the end point [23,24], the knotting and unknotting on suture procedures [25], or grasping and lifting on tissue retraction [26]. Ultimately, we selected three actions to be performed by the collaborative robot: center the image from the endoscope, indicate a place to suture, and stretch the thread to suture.…”
Section: Algorithm For Movement Detectionmentioning
confidence: 99%
“…The actions to test the collaborative robot take into account the various robotic actions covered by the literature [20], among which are the guidance of the laparoscopic camera for the safe movement of the endoscope [21] or a needle insertion [22], the prediction of the end point [23,24], the knotting and unknotting on suture procedures [25], or grasping and lifting on tissue retraction [26]. Ultimately, we selected three actions to be performed by the collaborative robot: center the image from the endoscope, indicate a place to suture, and stretch the thread to suture.…”
Section: Algorithm For Movement Detectionmentioning
confidence: 99%
“…Automated Suturing: Automation of suturing has been studied in the context of hierarchical models for multi-step task planning [11], multilateral manipulation of needle and suture [34], and interaction with deformable tissue [8,9].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Padoy et al showed execution of collaborative human-robot suturing, but the key sections requiring interactions such as needle insertion and hand-off were performed manually [26]. Similarly, Staub et al automated needle insertion into tissue for single-throw suturing [34].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Virtual constraints [2] and supervision of manipulation forces [3] minimize the risk of tissue damage. Augmentation of the patient with preoperative imaging modalities [4] and the associated information presentation, camera control and (partly) autonomous executed actions of error-prone and recurrent (sub-) tasks, such as knottying [5] or tissue piercing [6], have drawn the attention of researchers. This growing number of high level functionality that we might see in future (commercial) systems has to be executed, controlled and supervised by the human operator.…”
Section: Introductionmentioning
confidence: 99%